Enenterum kyphosi Yamaguti, 1970 and Enenterum petrae n. sp. (Digenea: Enenteridae) from kyphosid fishes (Centrarchiformes: Kyphosidae) collected in marine waters off eastern Australia - Huston, Daniel C.; Cutmore, Scott C.; Cribb, Thomas H. (Zootaxa, 2022)
Species of the digenean genus Enenterum Linton, 1910 (Lepocreadioidea: Enenteridae) are characterised primarily by their elaborate oral suckers, which are divided into varying numbers of anteriorly directed lobes, and their host-restriction to herbivorous marine fishes of the family Kyphosidae. We describe Enenterum petrae n. sp. from the brassy chub Kyphosus vaigiensis (Quoy & Gaimard) collected off Lizard Island, Great Barrier Reef, Queensland, Australia. Enenterum petrae n. sp. is readily differentiated from congeners by its unique oral sucker morphology, in having a minute pharynx, and the combination of a genital cap and accessory sucker. We also provide the first record of Enenterum kyphosi Yamaguti, 1970 from Australia based on material obtained from the blue sea chub Kyphosus cinerascens (Forsskål) collected off Lizard Island and North Stradbroke Island, Queensland. Morphologically, our specimens of E. kyphosi agree closely with descriptions of this species from Hawaii and South Africa, and despite lack of molecular data from outside of Australian waters, we consider all three reports to represent a single, widespread species. The first ITS2 and COI mtDNA gene sequences for species of Enenterum are provided and molecular phylogenetic analyses of 28S rDNA gene sequences place these species in a strongly-supported clade with the type-species of the genus, Enenterum aureum Linton, 1910. The oral suckers of both E. kyphosi and E. petrae n. sp. can be interpreted as having varying numbers of lobes depending on the particular specimen and how the division between lobes is defined. Scanning electron microscopical images improves understanding of the morphology of the enenterid oral sucker, and permits speculation regarding the evolutionary history leading to its specialisation in this lineage.